Malaria control in India: a national perspective in a regional and global fight to eliminate malaria - Guerin, P; Dhorda, M; Ganguly, N; Sibley, C (Medknow Publications, 2019)
Since the declaration of the vision of malaria eradication in 2007, the overall burden of malaria has been reduced substantially in many countries in the endemic world. This progress has, however, recently slowed worldwide and even an increase of morbidity and mortality has been observed in some regions. That reality has led to reflection on the strategy for malaria elimination, noting that focusing only on low transmission sites has competed with the efforts in countries that still have foci with high malaria burdens. This opinion piece outlines the collaboration of the ICMR-National Institute of Malaria Research (ICMR-NIMR) and other partner Institutions in India with the WorldWide Antimalarial Resistance Network (WWARN), one part of a global effort to manage the spread of Plasmodium falciparum parasites associated with antimalarial resistance.